DISASTER RISK REDUCTION IN SCHOOLS ENVIRONMENT - Tukino Tukino (Politeknik Kesejahteraan Sosial Bandung, 2023)
The territory of Indonesia is an area that is prone to disasters, both natural, non-natural and social disasters. The occurrence of various disasters in Indonesia resulted in loss of life and property, damage to educational facilities in the form of collapsing school buildings, and school children who were threatened not to be able to carry out learning in class. The National Disaster Management Agency (BNPB) noted that since the earthquake and tsunami in Aceh in 2004, and various disaster events up to 2014, in total more than 300,000 people died and more than 10,000 schools were affected by the disaster, either heavily damaged or collapsed (BNPB: 2014). Children are one of the most vulnerable groups when a disaster occurs. One way to protect children from disasters is to make disaster risk reduction a part of the school curriculum. This study was conducted using the secondary data research methods, with the locus of study on data from various parties regarding disaster risk reduction education in schools. The data collected was then analyzed using document analysis techniques. The results of the analysis conclude that social workers are needed in disaster risk reduction in schools environment